Electroencephalographic comparison of veterans with combat-related posttraumatic stress disorder and health subjects - Begić, Dražen (Array, 2001)
Various investigations prove the biological basis for post-traumatic stress disorder (PTSD). There are only a few quantitative electroencephalographic (qEEG) studies of patients with PTSD. The aim of this investigation is to find out whether there are differences in qEEG parameters between PTSD patients and healthy subjects. The experimental group was comprised of 18 veterans with PTSD, and 20 healthy non-veterans were included in the control group. After informed consent was obtained, they were investigated by qEEG recordings. The artifact-free EEG epoch was analyzed by fast Fourier transformation (FFT). Power values of particular frequency bands (delta, theta, alpha 1, alpha 2, beta 1, beta 2) were observed on the regions: Fp I, Fp2, F3, F4, F7, F8, C3, C4, T3, T4, T5, T6, P3, P4, O1 and O2. PTSD patients had increased theta activity over central regions, and increased beta activity. Beta 1 activity increased over frontal, central and left occipital regions ; beta 2 activity increased over frontal regions. No significant differences were noted between the PTSD and control group in delta and alpha activity. These results suggest a neurobiological basis for PTSD. Increased theta activity may help to explain changes in hippocampal volume. Various explanations (cortical hyperexcitability, prolonged wakefulness, or attention disturbances) have been offered for the beta activity increase observed in PTSD subjects.